Maternal hypertensive disorders are associated with increased use of respiratory support but not chronic lung disease or poorer neurodevelopmental outcomes in preterm neonates at <29 weeks of gestation. (25th January 2017) - Matić, Mara; Inati, Violet; Abdel‐Latif, Mohamed E; Kent, Alison L; ,
Abstract : Aim: To assess whether maternal hypertensive disorders in pregnancies result in higher respiratory requirements, risk of chronic lung disease (CLD) and poorer neurodevelopmental outcome in <29‐week premature neonates. Methods: This is a multicentre, retrospective cohort study, within a geographically defined area in Australia, served by a network of 10 neonatal intensive care units (NICUs), consisting of infants <29 weeks of gestational age who were admitted to NICUs between 1998 and 2004. Outcome measures included hospital survival, perinatal complications and functional disability at 2–3 years follow‐up. Results: A total of 2549 mothers and infants were included in the study; 379 (14.9%) mothers had hypertensive disorders during pregnancy. Follow‐up data were obtained for 1473 (74.8%) infants at 2–3 years. Infants exposed to pre‐eclampsia had a higher need for supplemental surfactant therapy (odds ratio (OR): 2.004, 95% confidence interval (CI): 1.51–2.66), longer duration of mechanical ventilation (7.0 days vs. 4.0 days), were associated with a higher incidence of CLD (OR: 1.40, 95% CI: 1.12–1.76) and received post‐natal steroids for CLD (OR: 1.82, 95% CI: 1.43–2.31) and home oxygen (OR: 1.47, 95% CI: 1.11–1.95). Multivariable analysis showed that hypertensive disease of pregnancy was not significantly associated with the development of CLD in this cohort (OR: 1.103, 95% CI: 0.845–1.441). Multivariable analysis of long‐term neurodevelopmental data available for the 1473 follow‐up infants showed no significant difference in outcomes with or without exposure to maternal hypertensive disease. Conclusion: Maternal hypertensive disease of pregnancy does not increase the risk of CLD or long‐term neurodevelopmental complications in infants born at <29 weeks of gestation.